KENISCAYAAN REVOLUSI ISLAM (Menggagas Ulang Doktrin Teologi Revolusi Islam Hasan Hanafi) - Haris Riadi (An-Nida', 2012)
Rethinking of Hasan Hanafi for theological doctrine on Islamic revolutionTheological revolution was initiated by Hasan Hanafi as a new model on Islamic principle doctrine known as “Tauhid”. He explains the principle and causes of losing spirit of Muslim world on tauhid and a dualistic worldview. Dualistic worldview is reflected in the repressive character of those who believe in one power and deny the other side. So, Hasan Hanafi tried to position the unity as a way of looking to overcome the crisis experienced by the Muslims and restore its civilization identity. To grow and return to the spirit of unity to revolution to Hasan Hanafi, the need to reconstruct the understanding of the main doctrines of Islam and in accordance with its development as done its predecessors. Since without doing the reconstruction of tawhid, the unity will remain bound by the normative understanding of the transcendent, only discuss the substance and nature of the gods itself. Thus, reconstruction is done so that unity can come down as human resistance force language other than Allah. But, before doing that task first of all need to trace the historical development of Islamic theology and naming by looking at the themes and discussions on theology. Then, critique it in order to formulate a revolutionary new theology as an offer of an alternative solution to the problem of humanity.